The Impact of Explicit Instruction on the Use of Discourse Markers in Classroom:: A Comparative Study of ESL Students - Fuseini, Kadir; Salifu, AbdulKadir; Iddrisu, Sulemana; Ahmed, Mustapha; Abdul Jalie, Sayibu (International Journal of Language Teaching and Education, 2026)
This study examines the effect of explicit instruction on English as a Second Language (ESL) students’ pragmatic competence, focusing on their use of discourse markers (DMs) such as “so,” “okay,” “oh,” “however,” and “well” in spoken interactions. A quasi-experimental design was applied, with Class A as the experimental group and Class B as the control group. Pre-test results revealed a minor difference in DM use, with Class A producing 32 instances and Class B 27. The marker “so” was most common, while “okay” appeared least. A pre-test t-test (t = 1.39, p = 0.203) indicated no significant difference, suggesting similar baseline proficiency. After explicit instruction for Class A, post-test results showed substantial improvement: Class A achieved a mean of 12.8 (SD = 1.92), compared to Class B’s 4.6 (SD = 1.14). A post-test t-test (t = 8.2, p = 0.001) confirmed significance. Findings underscore the value of explicit instruction in enhancing ESL learners’ pragmatic competence.